Water‐Promoted Palladium‐Catalyzed Asymmetric Ring‐Opening of Oxabenzonorbornadienes with Alkoxysilanes. Issue 1 (22nd November 2019) - Tan, Yun; Yao, Yongqi; Yang, Wen; Lin, Qifu; Huang, Guobao; Tan, Minxiong; Chen, Shuqi; Chen, Donghan; Yang, Dingqiao
Abstract: Water‐promoted palladium‐catalyzed asymmetric ring‐opening (ARO) reaction of oxabenzonorbornadienes with a wide variety of alkoxysilanes has been developed in a one‐pot fashion, yielding cis ‐1, 2‐dihydronaphthalen‐1‐ols in favourable yields (up to 98%) with gratifying enantioselectivities (up to 98% ee ) under mild conditions. To the best of our knowledge, it represents the first example in the ring‐opening reactions of oxabicyclic alkenes with alkoxysilanes. Furthermore, the cis ‐1, 2‐configuration of product was established by X‐ray diffraction analysis, and a possible mechanism for the present catalytic ring‐opening reaction was also proposed. Abstract :